Indigenous Pedagogies: Weaving Communities of Wonder (LEARNing Landscapes, 2022)
Indigenous metissage weaves together life writing, poems, scholarship, and images, as a way of sharing strands of my experience of how, while not innovative to us, Indigenous research methods and transformative, participatory pedagogies, such as dreaming, ceremony, making, and drumming, offer suggestions around ways in which to create communities of learning which are inviting for all learners. This is particularly so when we work in arts-based practices, approaches, and paradigms. These transformative Indigenous pedagogies have become the sites of rich, healing conversations with myself, with the land and waters, with my Ancestors, and All My Relations.
Keywords: Indigenous pedagogy; ceremony; arts-based practices; transformative practices; ethical relationality